The innovative business school : mentoring today's leaders for tomorrow's global challenges - Halkias, Daphne; Neubert, Michael, 1968-; Thurman, Paul W.; Adendorff, Christian; Abadir, Sameh (London : Routledge, 2021)
The Innovative Business School formulates a blueprint for the innovative business school of the next decade, with proposed areas of innovation which will train executives to transform the coming technological disruptions into an avenue for world economic development and prosperity. Offering a new model of business education, the book maps the way forward for business school innovators in exploring questions related to innovation and strategy needed on the part of academic and industry leaders and educators across demographic divides. The chapters cover an overall international and cross-cultural approach in examining the factors at play for business schools of the future and the challenges they face across a range of megatrends affecting today's business environment. The authors impress the need for stakeholders to strategically engage others in the business and education ecosystems through commitment to experimentation, innovation, and sustainable business strategy. Identifying such opportunities for development of a new model for business schools is important to educators and policymakers in preparing to leverage and contribute to existing megatrends to create shared value for regional economies and in new directions. The Innovative Business School is written for business schools' management and decision-makers, related stakeholders, universities, accreditation agencies, and postgraduate students.
PART 1 Innovating the Business School 1 Introduction: Will Business Schools be the Disrupter, or the Disrupted? 2 The Evolution of Business Schools: Past and Present 3 Transforming the MBA Curriculum for Industrial Revolution 4.0 4 Price-Setting Models for the Innovative Business School 5 Internationalization Strategies for the Innovative Business School 6 The Great Paradigm Shift: Business Schools Leading the Global Sustainability Agenda 7 The Innovative Business School: Looking Ahead and Forecasting Trends PART 2 The Future of the Business School: Innovative Voices from the Field 8 The Sustainability Initiative at IMD Business School, Switzerland 9 The M.Phil in Future Studies at University of Stellenbosch, South Africa 10 The MSc. in Digital Transformation Management and Leadership at ESCP Europe 11 A Gender Empowerment Initiative at the Enterprise Development Centre of Pan-Atlantic University, Nigeria 12 An Innovative Post Graduate Master of Business Administration in Rural Development at University of Allahabad, India 13 AI and Higher Education : Who is Teaching the Learners? 14 Not Just for Business: Sustainability Curricula at Columbia University 15 The Master of Data Science of the Department of Statistics and Actuarial Science at The University of Hong Kong 16 The Impact of Business Schools on Economic Growth in the MENA Region 17 Redesigning Business Education at European School of Management and Technology: ESMT Berlin 18 International School of Management Paris Connects with Business Beyond its Walls 19 The Universidad Paraguaya Alemana: An Innovative Business School in Latin America
OCLC-licensed vendor bibliographic record.
Keywords: Business education; Executives -- Training of; BUSINESS & ECONOMICS / Education; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Training